Comparison of two techniques of administering the Valsalva manoeuvre in patients under general anaesthesia: A randomised controlled study - Shagun B. Shah; Vineet Chaudhary; Rajiv Chawla; Uma Hariharan; Neha Ghiloria; Jitendra Kumar Dubey (Indian Journal of Anaesthesia)
Background and Aims: Surgeons often request a Valsalva manoeuvre (VM) at the end of surgery (head–neck surgery, craniotomy) to check haemostasis and to unmask covert venous bleeders. We aimed to compare an anaesthesia machine-generated objective technique for delivering VM under pressure-control (PC) mode with the traditional subjective technique of delivering VM in manual mode. Methods: This randomised controlled study included 60 adult patients randomised to manual (Group M) and controlled ventilation (Group C) groups. Our primary outcome measure was internal jugular vein (IJV) diameter at pre-determined time points (T0 = baseline, T1 = VM initiation, T2 = 20 s after VM initiation, T3 = immediately after VM release, and T4 = 1 min, T5 = 2 min and T6 = 5 min post-VM release). Secondary outcome measures included mean arterial pressure (MAP), heart rate, time to desired plateau airway pressure, number of patients with bleeders unmasked and surgeon satisfaction. Independent/paired sample t-tests were applied. Results are expressed as mean (standard deviation), mean difference (95% confidence interval), dotted box–whisker plots and trendlines. P <0.05 is considered statistically significant. Results: Mean differences in diameter changes in IJV (in centimetres) in the mediolateral and anteroposterior directions between Group C and Group M were -0.136 (-0.227, -0.044) and -0.073 (-0.143, -0.002), respectively. VM in the PC mode produced more significant IJV dilatation (P = 0.004, P = 0.044). MAP at T0 and T1 was comparable. At T2 and T3, there was a more significant fall in MAP in Group C versus Group M (P = 0.018 and P = 0.021, respectively). At T4, T5 and T6, MAP was comparable. Conclusion: Performing VM in PC mode is a better technique based on IJV diameter, haemodynamics, bleeder unmasking and surgeon satisfaction.